1991
DOI: 10.1029/90gl02298
|View full text |Cite
|
Sign up to set email alerts
|

The solar and equatorial QBO influences on the stratospheric circulation during the early northern‐hemisphere winter

Abstract: A case study was conducted to investigate the mechanism of how the solar cycle and the equatorial quasi‐biennial oscillation (QBO) influence the stratospheric circulation during the Northern‐Hemisphere winter. It was found that the solar and QBO influences on the stratospheric jet exist rather independently in the upper stratosphere during December. The mean‐zonal wind anomalies produced in early winter persist by deformation until late winter through wave‐mean flow interactions with planetary waves. The modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…The movement of the developing polar vortex anomaly to higher latitudes with time during the winter can also be seen in the present data, especially at midlatitudes (cf. Kodera, 1991;James and Dodd, 1996). Negative anomaly maxima of fv*+DF in the polar regions can be found near the latitude of the maximum mean zonal wind anomalies, so that the negative anomalies are likely to explain the difference found in the polar-night jet between the QBO phases.…”
Section: Wave Behaviormentioning
confidence: 87%
“…The movement of the developing polar vortex anomaly to higher latitudes with time during the winter can also be seen in the present data, especially at midlatitudes (cf. Kodera, 1991;James and Dodd, 1996). Negative anomaly maxima of fv*+DF in the polar regions can be found near the latitude of the maximum mean zonal wind anomalies, so that the negative anomalies are likely to explain the difference found in the polar-night jet between the QBO phases.…”
Section: Wave Behaviormentioning
confidence: 87%
“…In spite of some attempts (e.g., Kodera, 1991) to explain this relation, the real mechanism of this relation continues to be unclear and awaits further investiga- March means of index g 1 and the equatorial zonal winds at 50 hPa and 30 hPa respectively. Running correlations are calculated using 3-year window width.…”
Section: Discussionmentioning
confidence: 99%
“…Following this assumption, the possibility of connection between the wintertime (January to March) variations of total ozone and the sunspot numbers at simultaneous moment in the QBO phase is investigated in the present study. This research is based on the results of Labitzke (1987), Labitzke and van Loon (1988, 1993, Kodera (1991Kodera ( , 1993, Kodera et al (1991), van Loon andLabitzke (1994), Soukharev (1997a) which were obtained by analysing a possible connection between the meteorological parameters in the winter stratosphere and the sunspot numbers when the data are grouped according to the phases of QBO. Thus, these authors have noted that during the phase of QBO there is positive correlation between the variations of temperature and geopotential heights in the winter polar stratosphere, and the solar activities.…”
Section: Introductionmentioning
confidence: 99%
“…In both early and late winter months, they found deeper polar vortices and stronger polar night jets in the W than in the E. Labitzke (1982) showed that the polar lower stratosphere is colder in the W than in the E, and that major warmings do not occur in the W, except near the maxima of the solar cycle. Such interannual variability in the extratropical stratosphere associated with the equatorial QBO has been called the More recent observational studies (e.g., Labitzke, 1987;van Loon, 1988, 1992a;Labitzke and Chanin, 1988;Kodera, 1991) showed associations of the extratropical stratospheric circulation with the QBO and the 11-year solar cycle, though other authors (e.g., Salby and Shea, 1991) commented on the statistical significance of the associations. Labitzke (1987) and van Loon (1988, 1992a) showed that the north-polar temperature at 30 hPa has a correlation positive with the sunspot number in the W, but negative in the E.…”
Section: Introductionmentioning
confidence: 99%